Conference summary & recent advances: The 8th Conference on Metal Toxicity and Carcinogenesis - Zhou, Xixi (Biol Trace Elem Res, 2015)
Diseases caused by occupational and environmental exposure to metals are a public health concern. The underlying molecular mechanisms of metal toxicity and carcinogenicity remain largely unknown. Over 130 scientists attended the 8(th) Conference on Metal Toxicity and Carcinogenesis, presenting their various research concerns and recent findings to stimulate interactions and collaborations among scientists in the field. Several major areas were emphasized, including human & population studies, molecular & cellular mechanisms, biological targets, epigenetic effects, metabolism, and metal mixtures. Here we summarize presentations at the conference sessions and highlight the attendees’ latest work published in this special issue of Biological Trace Element Research.